Report of a floral visitor of Cypripedium irapeanum (Orchidaceae) in Tepoztlán, Morelos, Mexico - Miguel Ángel Lozano Rodríguez; José Luis Alanís Méndez; Oswaldo Javier Enciso Díaz; Juan Manuel Pech Canché (Polibotánica)
The process and participating actors of pollination have fascinated many scholars since the time of Darwin. Nevertheless, for many species of orchids, the identity of the pollinator or the purpose of floral visits remains unknown. Cypripedium (Orchidaceae) is a genus of worldwide distribution that presents a broad range of colors and sizes. Three species are reported in Mexico: C. dickinsonianum, C. irapeanum and C. molle. However, there is very little information regarding the ecological interactions of these species. Firstly, a preliminary bibliographic review was conducted in order to compile information pertaining to the pollinators and floral visitors of the genus Cypripedium. Secondly, a population of C. irapeanum was monitored in a pine-oak forest at 1680 m.a.s.l. in the municipality of Tepoztlán, in Morelos, Mexico. The municipality of Tepoztlán in Morelos, Mexico, hosts a population of approximately 250 individuals of the species C. irapeanum. During a visit to this site in July 2015, two specimens of bees, belonging to the genus Lasioglossum subgenus Eickwortia, were found exiting from the apertures of the rear part of the C. irapeanum labellum. This event was photographed and one bee specimen was collected and identified to species, thus contributing to the first record of a floral visitor to this species of orchid. Lasioglossum nyctere is a floral visitor and possibly a pollinator of C. irapeanum. Future studies should confirm whether or not this bee is indeed a pollinator of the orchid.